2018
DOI: 10.1039/c8cp01463a
|View full text |Cite
|
Sign up to set email alerts
|

Single-layer ZnMN2 (M = Si, Ge, Sn) zinc nitrides as promising photocatalysts

Abstract: Searching for two-dimensional semiconductor materials that are suitable for visible-light photocatalytic water splitting provides a sustainable solution to deal with the future energy crisis and environmental problems. Herein, based on first-principles calculations, single-layer ZnMN2 (M = Si, Ge, Sn) zinc nitrides are proposed as efficient photocatalysts for water splitting. Stability analyses show that the single-layer ZnMN2 zinc nitrides exhibit energetic and dynamical stability. The electronic properties r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…The optimized lattice constant and bond lengths are in good agreement with previous results. 46 The dynamical stability of the ZSN is verified by calculating its phonon band dispersion, which is depicted in Figure 1b. The monolayer of ZSN is found to possess dynamical stability in its free-standing form as examined by the phonon band dispersions through the whole BZ.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The optimized lattice constant and bond lengths are in good agreement with previous results. 46 The dynamical stability of the ZSN is verified by calculating its phonon band dispersion, which is depicted in Figure 1b. The monolayer of ZSN is found to possess dynamical stability in its free-standing form as examined by the phonon band dispersions through the whole BZ.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…121 Recent computational work has predicted that singlelayer Zn−IV−N 2 compounds could be used for water-splitting applications. 122 Related materials, such as Zn 2 SbN 3 , have been identified as candidates for one of the water-splitting half reactions, in this case the hydrogen evolution reaction, rather than overall water splitting. 123 While cation ordering has yet to be investigated in materials for these applications, the band gap tuning described above for LED and PV applications could also be employed to modify band gap for these applications, possibly allowing tuning of band edge positions to improve particular photocatalytic reactions.…”
mentioning
confidence: 99%
“…Among these, ZnGeN 2 is the most well-explored, mainly in the form Zn 1– x Ge x N 2– y O y , which has been shown to be an effective catalyst for overall water splitting. , It has also been identified as a candidate material for some CO 2 reduction processes , and for pollutant decomposition under visible light . Recent computational work has predicted that single-layer Zn–IV–N 2 compounds could be used for water-splitting applications . Related materials, such as Zn 2 SbN 3 , have been identified as candidates for one of the water-splitting half reactions, in this case the hydrogen evolution reaction, rather than overall water splitting .…”
mentioning
confidence: 99%
“…In particular, mechanical strain or an external electric eld are effective and practical ways to adjust the electronic properties of a 2D semiconductor. [45][46][47][48][49][50][51][52] For example, Bai et al have shown that single-layer ZnGeN 2 could be effectively tuned to provide a better match with the redox potentials of water and to enhance light absorption in the visible-light region at a tensile strain of 5%. 49 Edalati et al suggested that CsTaO 3 and LiTaO 3 exhibited optical bandgap narrowing and $2.5 times enhancement of photocatalytic hydrogen generation by straining.…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47][48][49][50][51][52] For example, Bai et al have shown that single-layer ZnGeN 2 could be effectively tuned to provide a better match with the redox potentials of water and to enhance light absorption in the visible-light region at a tensile strain of 5%. 49 Edalati et al suggested that CsTaO 3 and LiTaO 3 exhibited optical bandgap narrowing and $2.5 times enhancement of photocatalytic hydrogen generation by straining. 50 Wang et al reported that the biaxial strain tuned the bandgap and band alignment of a 2D CdS/ g-C 3 N 4 heterostructure for visible-light photocatalytic water splitting and accelerated the separation of photogenerated carriers and improved the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%